A systematic review of biochar research, with a focus on its stability in situ and its promise as a climate mitigation strategy. - Noel P Gurwick; Lisa A Moore; Charlene Kelly; Patricia Elias (PLoS ONE)
Background Claims about the environmental benefits of charring biomass and applying the resulting "biochar" to soil are impressive. If true, they could influence land management worldwide. Alleged benefits include increased crop yields, soil fertility, and water-holding capacity; the most widely discussed idea is that applying biochar to soil will mitigate climate change. This claim rests on the assumption that biochar persists for hundreds or thousands of years, thus storing carbon that would otherwise decompose. We conducted a systematic review to quantify research effort directed toward ten aspects of biochar and closely evaluated the literature concerning biochar's stability. Findings We identified 311 peer-reviewed research articles published through 2011. We found very few field studies that addressed biochar's influence on several ecosystem processes: one on soil nutrient loss, one on soil contaminants, six concerning non-CO2 greenhouse gas (GHG) fluxes (some of which fail to support claims that biochar decreases non-CO2 GHG fluxes), and 16-19 on plants and soil properties. Of 74 studies related to biochar stability, transport or fate in soil, only seven estimated biochar decomposition rates in situ, with mean residence times ranging from 8 to almost 4,000 years. Conclusions Our review shows there are not enough data to draw conclusions about how biochar production and application affect whole-system GHG budgets. Wide-ranging estimates of a key variable, biochar stability in situ, likely result from diverse environmental conditions, feedstocks, and study designs. There are even fewer data about the extent to which biochar stimulates decomposition of soil organic matter or affects non-CO2 GHG emissions. Identifying conditions where biochar amendments yield favorable GHG budgets requires a systematic field research program. Finally, evaluating biochar's suitability as a climate mitigation strategy requires comparing its effects with alternative uses of biomass and considering GHG budgets over both long and short time scales.